2020
DOI: 10.1017/s0021859620000994
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality indicators as influenced by 5-year diversified and monoculture cropping systems

Abstract: Increasing crop diversity has been highly recommended because of its environmental and economic benefits. However, the impacts of crop diversity on soil properties are not well documented. Thus, the present study was conducted to assess the impacts of crop diversity on selected soil quality indicators. The cropping systems investigated here included wheat (Triticum aestivum L.) grown continuously for 5 years as mono-cropping (MC), and a 5-year cropping sequence [(wheat–cover crop (CC)–corn (Zea mays L.)–pea (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 112 publications
(156 reference statements)
2
7
1
Order By: Relevance
“…The overall higher BD at Hohenschulen compared to Harste was likely caused by the higher sand content at Hohenschulen. At Harste, AS was slightly higher for WM than for W1, which is in contrast to Feng et al (2020), who reported growing wheat in a crop rotation compared to monoculture cropping increased the AS in a loamy soil in 0-5 cm soil depth, while this effect was not detectable in 5-15 cm soil depth. However, since in our study values for W2, also from the crop rotation, were even higher than for W1, the effect of rotational diversity seems to be modified by other factors.…”
Section: Effects Of the Crop Rotational Position Of Wheat On Soil Str...contrasting
confidence: 87%
See 2 more Smart Citations
“…The overall higher BD at Hohenschulen compared to Harste was likely caused by the higher sand content at Hohenschulen. At Harste, AS was slightly higher for WM than for W1, which is in contrast to Feng et al (2020), who reported growing wheat in a crop rotation compared to monoculture cropping increased the AS in a loamy soil in 0-5 cm soil depth, while this effect was not detectable in 5-15 cm soil depth. However, since in our study values for W2, also from the crop rotation, were even higher than for W1, the effect of rotational diversity seems to be modified by other factors.…”
Section: Effects Of the Crop Rotational Position Of Wheat On Soil Str...contrasting
confidence: 87%
“…Concerning WW crop rotations, Feng et al (2020) found in a 17-year-long study that crop diversity of wheat rotations improves AS, while lowering dry BD. Pranagal and Wo źniak (2021) did not detect differences between wheat monoculture (WM) and wheat grown as rotational crop regarding soil physical properties after 30 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the moderator “number of main crop species in the rotation”, which can be seen as a proxy for main crop diversity, followed a positive trend (Figure 9d,f, respectively). Diverse crop rotations, in comparison to monocropping, provide abundant plant biomass inputs and rhizodeposits, which are known to stimulate microbial growth and, hence can promote MBC accrual (Feng et al, 2020; Motta et al, 2007). Additionally, crop rotations are recognized for their capacity to enhance soil structure, providing an environment favourable to microbial development (Kennedy, 1999) and hence MBC accrual.…”
Section: Discussionmentioning
confidence: 99%
“…There is mixed conclusion on the impact of crop rotation experimental duration on soil properties [13]. Numerous studies have reported that the influence of crop rotation on soil quality improvement depends on the type of crops cultivated in a particular rotation system [14,15].…”
Section: Introductionmentioning
confidence: 99%